Characteristics of Ship-Emitted VOCs and Their Contributions to Urban Atmospheric VOCs in Guangzhou, China - Xueying Zeng; Liwei Wang; Haining Wu; Chenglei Pei; Hong Ju; Junjie He; Ming Liu; Mei Li; Daiwei Chen; Yongjiang Xu; Wenlong Tang; Jinchi Li; et al. (Toxics, 2025)
With the implementation of China’s low-sulfur fuel policy, the characteristics of volatile organic compounds (VOCs) emitted from ship exhausts have changed significantly, and the influence of these emissions on the local atmosphere of port cities needs to be evaluated. In this study, the characteristics of localized source profiles of ship-emitted VOCs with respect to different ship types, fuel types, and engine operating conditions were analyzed in Guangzhou Port. Oxygenated VOCs (OVOCs) dominated in ferry (91.1%), cargo ship (87.0%), and tugboat (54.4% ± 7.9%) emissions (diesel fuel), while alkanes (56.3% ± 1.6%) and alkenes (36.0% ± 0.9%) were major species in multi-purpose ship (LNG fuel) emissions. These results suggest the dominance of OVOCs in the exhaust emissions of diesel-type ships and the prominent difference in ship-emitted VOCs between diesel and LNG fuel ships, which also influenced the emission characteristics of VOCs from main and auxiliary engines. Based on the measured source profiles, ship emissions contributed 18.2% ± 0.8% (summer), 8.7% ± 1.9% (winter), 6.0% ± 1.1% (spring), and 5.6% ± 1.7% (autumn) to VOCs in the port area, and 7.8% ± 1.5% in July and 5.0% ± 0.5% in September in the urban area. An air mass trajectory analysis revealed that the south wind transported the ship exhaust emissions to the port area and inland urban area, which explained the higher contributions of ship emissions in summer and more ship emissions received in the port area than in the urban area. Therefore, estimating the influence of ship emissions on ambient air quality in port cities requires integrating local ship source profiles, locations, and meteorological conditions. This study provides insights into the ship-emitted VOC characteristics given China’s low-sulfur fuel policy and their differential contributions to urban atmospheric VOCs.